Phytochemical and antimicrobial activity screening of seeds of Psoralea corylifolia L. - M.M.V. Baig (Elsevier, 2022)
Background: Psoralea corylifolia L., a member of the family Fabaceae is found all over the world. The seeds of P. corylifolia forms an integral part of traditional medicine in China and India, to treat different illnesses. In our recent survey of traditional healers in the Marathwada region, Maharashtra, India, it was found that P. corylifolia has been used for many skin diseases when applied externally and also for dysentery and diarrhoea. The work was aimed at evaluating the antimicrobial activity of seeds of P. corylifolia against bacteria and fungi associated with these human ailments. Method: The seeds were extracted with ethanol and this extract were tested against two bacterial viz. Escherichia coli and Staphylococcus aureus and two fungi, the yeast Candida albicans and the dermatophyte Trichophyton rubrum. The ethanol extract was subjected to separation of compounds by HPLC and LC-MS and these separated compounds were identified based on the mass data. The Minimum Inhibitory Concentration (MIC), median Inhibitory Concentration (IC50), and Minimum Bactericidal Concentration (MBC) / Minimum Fungicidal Concentration (MFC) values of crude extract as well of purified compound were determined. Results: The seed extract showed high antimicrobial properties against the bacteria E. coli and S. aureus, the fungi, C. albicans and T. rubrum. The seed extract was further subjected to HPLC and LC-MS analysis. The extracts showed analogous compounds in their chromatograms as purified compound. These compounds were identified as bakuchiol, bavachalcone, bavachromene, corylifol A, corylin, isobavachalcone, isopsoralen, psoralen, and psoralidin. Conclusions: The seed extract and its fractions of P. corylifolia possess antibacterial properties against E. coli and S. aureus along with antifungal properties against C. albicans and T. rubrum, giving support to the use of the seed by traditional healers for gastric and skin ailments. The antimicrobial properties are attributed to the phytochemical constituents of the plant.